Myocardin-related transcription factor A (MRTFA) regulates the fate of bone marrow mesenchymal stem cells and its absence in mice leads to osteopenia - Hejiao Bian; Jean Z. Lin; Chendi Li; Stephen R. Farmer (Elsevier, 2016)
Objective: Arising from common progenitors in the bone marrow, adipogenesis and osteogenesis are closely associated yet mutually exclusive during bone marrow mesenchymal stem cell (BMSC) development. Previous studies have shown that morphological changes can affect the early commitment of pluripotent BMSCs to the adipose versus osteoblastic lineage via modulation of RhoA activity. The RhoA pathway regulates actin polymerization to promote the incorporation of globular actin (G-actin) into filamentous actin (F-actin). In doing so, myocardin-related transcription factors (MRTFs) dissociate from bound G-actin and enter the nucleus to co-activate serum response factor (SRF) target gene expression. In this study, we investigated whether MRTFA/SRF is acting downstream of the RhoA pathway to regulate BMSC commitment in mice. Methods: The effects of knocking out MRTFA on skeletal homeostasis was studied in MRTFA KO mice using micro-CT, QPCR and western blot assays. To determine how MRTFA affects the mechanisms regulating BMSC fate decisions, primary bone marrow stromal cells from WT and MRTFA KO mice as well as C3H10T1/2 cell lines were analyzed in vitro. Results: Global MRTFA KO mice have lower whole body weight, shorter femoral and tibial lengths as well as significantly decreased bone mass in their femurs. BMSCs isolated from the KO mice show increased adipogenesis and reduced osteogenesis when compared to WT littermates. KO mice, particularly females, develop osteopenia with age, and this was enhanced by a high fat diet. Over-expression of MRTFA or SRF enhances osteogenesis in CH310T1/2 cell lines. Sca1+, CD45− cells from KO marrow express lower amounts of smooth muscle actin (SMA) and TAZ/YAP target genes compared to WT counterparts. Conclusion: This study identified MRTFA as a novel regulator of skeletal homeostasis by regulating the balance between adipogenic and osteogenic differentiation of BMSCs. We propose that MRTFA promotes the osteogenic activity of TAZ/YAP by maintaining SMA production in BMSCs. Keywords: Mesenchymal stem cells, Myocardin-related transcription factor A (MRTFA), Serum response factor (SRF), Osteoporosis, Bone formation, Lineage commitment